Implementasi Penertiban Kawasan Parkir Di Kota Bengkulu - Sariningsih, Marida; Lorita, Evi; Imanda, Antonio; Siswati, Atiek (Jurnal Multidisiplin Dehasen (MUDE), 2023)
This study aims to evaluate the implementation of parking area regulation in Bengkulu City, specifically on Soeprapto Street, which is a central hub of public activity with high traffic density and parking retribution potential. The research employs a descriptive qualitative approach using observation, in-depth interviews, and documentation as data collection methods. The findings reveal that the implementation of parking retribution policy in Bengkulu City still faces several obstacles, such as weak bureaucratic structures, limited human resources and facilities, poor discipline among parking attendants, and lack of communication and supervision from relevant agencies. The study also uncovers illegal levies and discrepancies between parking fees and the established regulations. The theoretical framework is based on George C. Edward III’s model of policy implementation, which includes four key variables: communication, resources, disposition, and bureaucratic structure. The study recommends a comprehensive evaluation of the parking retribution system, enhancement of human resource capacity, and stricter law enforcement to achieve an orderly and transparent parking management system.